Development of Incompletely Fused Carpels in Maize Ovary Revealed by miRNA, Target Gene and Phytohormone Analysis - Li, Hongping; Peng, Ting; Wang, Qun; Wu, Yufeng; Chang, Jianfeng; Zhang, Moubiao; Tang, Guiliang; Li, Chaohai (Frontiers in Plant Science, 2017)
Although the molecular basis of carpel fusion in maize ovary development remains largely unknown, increasing evidence suggests a critical role of microRNAs (miRNAs). In this study, a combination of miRNA sequencing, degradome and physiological analyses was used to characterize carpel fusion development in maize ovaries showing incompletely (IFC) and completely fused carpels (CFC). A total of 162 known miRNAs distributed across 33 families were identified, of which 20 were differentially expressed. In addition, 53 miRNA candidates were identified, of which 10 were differentially expressed in the IFC and CFC ovaries. In degradome analysis, a total of 113 and 11 target genes were predicted for the known and novel miRNAs, respectively. Moreover, 24 (60%) target genes of the differentially expressed known miRNAs were found to code transcription factors, including auxin response factor (ARF), TB1-CYC-PCFs (TCP), APETALA2 (AP2), growth regulating factor (GRF), MYB, NAC and NF-YA, all of which have been shown to play a role in carpel fusion development. Correlation analysis of these differentially expressed known miRNAs and their targets with phytohormone signals revealed significant correlations with at least one phytohormone signal, the main regulator of carpel fusion development. These results suggest that incomplete carpel fusion is partly the result of differential expression of certain miRNAs and their targets. Overall, these findings improve our knowledge of the effect of miRNA regulation on target expression, providing a useful resource for further analysis of the interactions between miRNAs, target genes and phytohormones during carpel fusion development in maize.